KOMUNITAS FLORISTIK DAN SUKSESI VEGETASI SETELAH ERUPSI 2010 DI GUNUNG MERAPI JAWA TENGAH - Afrianto, Whisnu Febry; Hikmat, Agus; Widyatmoko, Didik (Perhimpunan Biologi Indonesia, 2016)
ABSTRACTSuccession dynamics (as a complex interaction and relationship between environment and species) is a crucial ecological process for managing and restoring habitats and ecosystems. This research was conducted at several locations based on the damage levels occurred due to the 2010 eruption of Mount Merapi: heavily damaged site was chosen at the Cangkringan Resort (consisting of both open and covered areas) and the Kemalang Resort, medium damage site was located at the Dukun Resort, and minor damage/relatively intact site was situated at the Selo Resort. A total of 135 plant species belonging to 64 families were recorded from all locations during the study. The Mount Merapi eruption occurred in 2010 had significantly impacted on the floristic community structure and condition. Canonical Correspondence Analysis (CCA) was used to analyze the relationships between environmental variables and the existing plant species conditions. The results indicated that different abiotic environment conditions (variables) significantly influenced species compositions and conditions. The covered area (?= 0:49; p= 0.002; F= 10:35) and the elevation factor (?= 0:32; p= 0.002; F= 7:08) provided the highest impact on vegetation conditions. Meanwhile, the relationships and correlations between edaphic factors and floristic community conditions varied from site to site.Key words: Abiotic environment, floristic community, succession, Mount Merapi, restoration